Who Supports the Successful Implementation and Sustainability of Evidence‐Based Practices? Defining and Understanding the Roles of Intermediary and Purveyor Organizations. Issue 149 (September 2015) - Franks, Robert P.; Bory, Christopher T.
Abstract: Research on implementation science has increased significantly over the past decade. In particular, psychologists have looked closely at the value and importance of bridging the gap between science and practice. As evidence‐based practices (EBPs) become more prevalent, concrete mechanisms are needed to bring these scientifically supported treatments and interventions to community‐based settings. Intermediary and purveyor organizations (IPOs) have emerged in recent years that specialize in bringing research to practice. Using a framework developed by Franks (2010 ), this descriptive study surveyed respondents that self‐identified as IPOs and focused on identifying shared definitions, functions, and activities. Results indicated that seven descriptive roles previously identified were supported by this survey and many common shared activities, goals, and functions across these organizations were observed. Further, these organizations appear to be influenced by the growing field of implementation science. Limitations and implications of this study are discussed. © 2015 Wiley Periodicals, Inc.